86 Mitral regurgitation in acute heart failure: prevalence and response to treatment. (17th July 2020) - Victor, Kelly; Bangash, Fatima; Stylianidis, Vasileios; Hancock, Jane; Monaghan, Mark; Piper, Susan; Byrne, Jonathan; McDowell, Garry; Redwood, Simon; McDonagh, Theresa; Prendergast, Bernard; Carr-White, Gerald
Abstract : Heart failure (HF) affects an estimated 90 000 people within the UK and 26 million worldwide. As a consequence of ventricular remodelling, significant mitral regurgitation (MR) is common in patients with HF, further contributing to poor prognosis, frequent hospitalisation, and higher rates of mortality. Conventional treatment options for HF patients with MR include medical therapy, cardiac resynchronisation and conventional mitral valve surgery, with transcatheter mitral valve repair reserved for symptomatic patients with left ventricular dysfunction and multiple comorbidities, considered high surgical risk. Aim: Our objectives were to determine: (1) the proportion of patients with an acute HF admission, an EF of <50% and moderate or more mitral regurgitation; (2) the effectiveness of optimal medical therapy in reducing the severity of MR and symptoms for these patients; (3) the number of patients with moderate or more MR, an EF <50% and symptoms despite optimal medical therapy. Method: We performed a retrospective analysis of all patients who presented with acute HF to two large London based tertiary centres over a five year period. Based on a combination of electronic care records, national registry data, and UK Office of National Statistics (ONS) mortality data, we determined baseline symptoms, symptom progression, and co-morbidities. Echocardiography data was used to assess the degree of MR and left ventricular systolic function (EF). Where patients underwent subsequent echocardiographic examinations on maximally tolerated medical therapy, the change in the degree of mitral regurgitation, ejection fraction and symptoms (NYHA class) was examined. Logistic regression was used to assess the impact of age, EF and comorbidities. Results: Over a five-year period (Jan 2012 – Dec 2017), 1884 patients presented with acute HF. Of this cohort, 302 (16%) had moderate or more MR and an EF of <50%. Mortality amongst patients with moderate or more MR was 29.9% at one year (compared to 26.9% for those with less than moderate MR, p=0.058). Of this cohort, 45% had sufficient clinical and echocardiographic paired follow up data to enable assessment of the effects of optimal medical therapy. This analysis showed, despite optimal medical therapy, all 135 patients still had moderate or more mitral regurgitation. When compared with previous echocardiography data, 11 (8.15%) patients showed a reduction in the severity of MR which meant 92% (124) of patient with MR either saw no improvement or worsening of their MR severity. Of those with severe MR, 23% (7) demonstrated an improvement in the degree of MR following optimal medical therapy. Clinically 70 (51.4%) patients had an improvement in symptoms. There was significant improvement in the NYHA class pre and post optimisation of medical therapy (p<0.001) across all grades of MR. Despite optimal medical therapy, 124 (92%) patients with moderate or more MR, EF <50% remained symptomatic. Conclusions: A large portion of patients who present with acute heart failure have moderate or more MR. Although medical therapy is effective in providing some relief from symptoms, the large majority of patients continue to have moderate or more mitral regurgitation. We propose a portion of these patients are potential candidates for transcatheter mitral valve repair according to current international guidelines, and should be considered for further intervention. Conflict of Interest: Nil